Assisting the Inquirer in Identifying Al-Maqatil, and the Supporting Evidence By Abu Abdullah Mohamed Bin Ahmed Bin Mohamed Bin Ali Bin Ghazi Al-Miknasi, dated (919 H). A Study and Investigation (Journal of Humanitarian and Applied Sciences, 2023)
Many scholars of Al-Malikiyah were interested in writing on separate jurisprudential matters, some of whom even singled them out for authorship, such as the prose, the versified, the detailed, and the simplified. Among those scholars who composed on separate matters was the venerable Sheikh "Abu Abdullah Mohamed Bin Ahmed Bin Mohamed Bin Ali Bin Ghazi Al-Miknasi (919 H(.,named after his hometown of Miknasah Al-Zaytoun. The Sheikh's words were easy and concise. In his book, the Agreed upon Maqatil (parts of the body that leads to death), he mentioned that they are five, as well as the signs of life, which he mentioned as five. He also adhered to the well-known doctrine after mentioning the difference in the same matter. The Sheik defined some of the jurisprudential terms that needed to be clarified: "Marrow: white sweat extended into the back and neck.)"In this paper, the researcher relied on a number of jurisprudential methodologies, including the descriptive method in describing the author and what was included, the documentary method: attributing transcripts, statements, and producing verses and hadith, as well as analytical methods: analyzing the author's words and commenting on them. The findings revealed that Ibn Ghazi's book was based on Ibn Rushd method in the introductions, as he guided many jurisprudential issues related to the execution of Al-Maqatil.
Keywords: Al-Maqatil; strangled; partially eaten; marrow